Poverty, government transfers, and the business cycle: evidence for the United States - Dierk Herzer; Rainer Klump (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
We examine the impact of government transfers and the business cycle on poverty in the United States in the context of a poverty function that includes the official poverty rate, three types of government transfers, real wages, the number of female-headed families, and a business cycle variable. Using cointegration techniques, we find – contrary to most previous studies – that government transfer programs play an important poverty-reducing role. In addition, the findings suggest that the business cycle is one of the key variables in explaining poverty in the US. Furthermore, the empirical results show that the size and composition of public transfer payments change over the business cycle. We also find poverty to have a significant effect on government transfers, the business cycle, and the structure of households.
Keywords: 330